Rare presentation of triangular intermuscular space sentinel lymph node in truncal melanoma of the back - Stojanoski, Sinisa; Nikolovska, Bisera; Manevska Nevena; Makazlieva Tanja; Pejkova, Sofija; Miladinova Daniela (My University, 2019)
Abstract Background: Sentinel lymph node biopsy procedure in malignant melanoma is considered as a staging modality and significantly decreases surgical morbidity and improves patient staging. The status of triangular intermuscular space lymph nodes gains an increased predictive role in grading truncal melanomas of the back and modulation of postoperative therapeutic protocols. If positive, almost always the same are associated with worse disease outcome. Nevertheless, the clinical significance of triangular intermuscular space lymph node micro-metastases and their management, up to date, remains poorly characterized, especially related to the ipsilateral or contralateral axillary node basin. Aim: The aim of this study is to present a rare case of male patient clinically diagnosed as stage II nodal melanoma of the back with concomitant scintigraphic detection of triangular intermuscular space and contralateral axillary sentinel lymph nodes. Methods: Dual method of planar and SPECT/CT scintigraphic sentinel lymph node detection with 99mTc-SENTI-SCINT, intraoperative gamma probe detection and radioguided surgery were used. Case report: We present a case of clinically diagnosed stage II nodal melanoma of the back with concomitant scintigraphic detection of intermuscular space and contralateral axillary sentinel lymph nodes. Histopathological evaluation of the extirpated nodes, performed by hematoxylin and eosin staining and immunohistochemistry section analyses revealed micro-metastases in the intermuscular space nodes and no metastatic involvement of the contralateral axillary node. Conclusions: Detection of intermuscular space lymph node metastases improves the N (nodal) grading of malignant melanoma by selecting a high risk subgroup of patients with no metastatic involvement of the ipsilateral or contralateral axillary node basin.
Keywords: gamma detection probe; intermuscular space lymph nodes; malignant melanoma; sentinel lymph node